Chaotic spiral based reconfiguration scheme for the mitigation of power loss in solar photovoltaic (PV) systems - Karthick. B; M. Sudhakaran (Results in Engineering)
The performance of photovoltaic (PV) arrays is significantly compromised by partial shading, which leads to reduced energy output and the formation of hotspots that can damage the modules. As the global shift towards renewable energy intensities, optimizing solar energy utilization has become a pressing concern. This study is motivated by the need to enhance the efficiency of PV systems under varying shading conditions, which remains a critical challenge in the field of solar energy. Despite the efforts to reduce shading effects, the problem of providing uniform shadings across the PV arrays has not yet been effectively solved. For the first time, this research applies an image encryption technique called Chaotic Sub-Block Scrambling based on Spiral Transformation (CSBSST) for redistributing the shadings by reorganizing the array layout without affecting the electrical connectivity. The proposed method is benchmarked against three established configurations: Total-cross-tied (TCT), Chaos Baker Map (CBM), and Improved Odd Even Prime (IOEP). MATLAB based simulation for an (8 × 8) PV array under different partial shading has been considered with the comparison result of an experimental set up of (4 × 4) PV array using CSBSST; it is observed that the proposed CSBSST yields maximum Global Maximum Power Point (GMPP) for all the cases. An economic analysis also highlights exactly how this method can improve efficiency of energy, improve the revenue and solidifies CSBSST as the solution to problems associated with partial shading in PV systems. Therefore, the mentioned Chaotic Spiral-based Reconfiguration scheme reduces power loss (PL) in Solar PV substantially. Concerning the configuration with the above parameters, the PL is 200 W, the FF is attained to 0.65, and the power output is 2500 W at GMPP. These improvements confirm the suitability of the chaotic spiral based approach in improving the efficiency and performance of PV systems.